Higher maternal vitamin D concentrations are associated with longer leukocyte telomeres in newborns. Issue 1 (9th June 2017) - Kim, Jung‐Ha; Kim, Gwang Jun; Lee, Donghee; Ko, Jae‐Hong; Lim, Inja; Bang, Hyoweon; Koes, Bart W.; Seong, Byeongchan; Lee, Duk‐Chul
Abstract: Gestational vitamin D insufficiency is related with increased risks of various diseases and poor health outcomes later in life. Telomere length at birth or early in life is known to be a predictor of individual health. Both vitamin D and telomere length are related with various health conditions, and vitamin D concentrations are associated with leukocyte telomere lengths in women. We investigated the association between maternal vitamin D concentrations and newborn leukocyte telomere lengths. This cross‐sectional study included 106 healthy pregnant women without adverse obstetric outcomes and their offspring. We examined the maternal age, weight before pregnancy, health behaviours, and nutritional intakes, along with each newborn's sex and birthweight, and we measured maternal height, telomere length, total white blood cell count, and glycosylated haemoglobin as covariates. Pearson's correlation coefficients were calculated to evaluate the relationship between the baseline variables and newborn leukocyte telomere lengths. To confirm that there was an independent association between newborn leukocyte telomere lengths and maternal vitamin D concentrations, we performed a stepwise multiple linear regression analysis. Newborn leukocyte telomere lengths correlated positively with maternal leukocyte telomere lengths ( r  = .76, p  < .01), maternal 25‐hydroxyvitamin D concentrations ( r  = .72, p  < .01), maternal energy intakes ( r  = .22, p  = .03), and newborn body weights ( r  = .51, p  < .01). In the multivariate model, newborn leukocyte telomere lengths were associated with maternal vitamin D concentrations (β = .33, p  < .01). These findings suggest that the maternal vitamin D concentration during pregnancy may be a significant determinant of the offspring's telomere length.